Pengaruh Metode Inkuiri Terbimbing Terhadap Hasil Belajar IPA pada Siswa Kelas V SD Negeri 101928 Rantau Panjang - Sitorus, Akhirayanti; Hariati, Emy; Malinda, Leni (Tematik: Jurnal Penelitian Pendidikan Dasar, 2024)
This study aims to analyze the effect of the guided inquiry method on science learning outcomes of fifth-grade students at SD Negeri 101928 Rantau Panjang. The background of this research is based on the low science learning outcomes of students, which is attributed to the use of conventional teaching methods that do not actively engage students in the learning process. The main research question is: Does the implementation of the guided inquiry method improve students' science learning outcomes? This research uses a quasi-experimental method with a pretest-posttest control group design. The sample consists of 40 students, divided into an experimental group and a control group. Data collection was conducted through learning outcome tests before and after the intervention, and the data were analyzed using a t-test. The results showed that students who learned through the guided inquiry method had a significant improvement in their science learning outcomes compared to those taught through conventional methods. The t-test results indicated a significance value of 0.00 < 0.05, meaning the hypothesis was accepted. In conclusion, the guided inquiry method is effective in enhancing science learning outcomes for fifth-grade students.